A Framework for Resilient Community Microgrids: Review of Operational Strategies and Performance Metrics - Joy Dalmacio Billanes; Bo Nørregaard Jørgensen; Zheng Ma (Energies)
The growing frequency of extreme weather events and grid disruptions highlights the urgent need for resilient energy systems. Decentralized and autonomous, community microgrids offer reliable and adaptable solutions. However, existing research often isolates components or control methods, lacking a comprehensive synthesis of their interdependencies and resilience strategies. To address this gap, this study conducts a comprehensive scoping review to synthesize the current state of knowledge on community microgrids, focusing on their types, components, operational strategies, control methods, and performance indicators. The research identifies key microgrid subtypes, such as islanded, hybrid, multi-energy, and autonomous systems, and evaluates the role of critical components like energy storage systems and distributed energy resources in enhancing resilience. It also highlights performance indicators, including reliability, stability, and flexibility, that serve as benchmarks for resilience. A novel framework is proposed, integrating microgrid design and operational aspects into a cohesive model for resilience enhancement. This framework provides actionable insights for practitioners to optimize microgrid design, for policymakers to create adaptive regulations, and for researchers to address knowledge gaps in the field. The findings underscore the critical role of advanced control methodologies in improving adaptability and efficiency under diverse operational conditions. By addressing the lack of an integrated approach in the existing literature, this study contributes to advancing resilient energy systems, supporting the energy transition, and promoting energy security. Future research should validate the proposed framework through empirical studies and explore scalable, cost-effective solutions to enable widespread adoption.